Impact of Delivery Mode on Neonatal Serum Bilirubin Levels and Jaundice Risk in Melati Husada Women and Children Hospital, Malang - Wijaya, Andreas Budi; Tjahjono, Harjoedi Adji (Preventia: The Indonesian Journal of Public Health, 2025)
It is anticipated that between 60 and 80 percent of healthy, full-term newborns would exhibit idiopathic neonatal jaundice. Mode of delivery has recently been associated with idiopathic neonatal jaundice. As seen at Melati Husada Women and Children Hospital in Malang, the increasing number of caesarean section was followed by increased frequency of neonatal hyperbilirubinemia. This hyperbilirubinemia should be resolved within two weeks, therefore, prolonged jaundice should be deeply investigated. This research aimed to investigate the relationship between mode of delivery and neonatal serum bilirubin at 48 hours after birth at Melati Husada Women and Children Hospital in Malang. During observational cross-sectional study from August 2016 to February 2017, 167 newborns were enrolled and classified into two groups based on the delivery method (caesarean section and vaginal delivery). The 48 hours total bilirubin levels were measured and compared. The data was analyzed using Independent T-Test. Subjects (n is 167) from this study were 51.5 percent male and 48.5% female. About 64.1 percent subjects were delivered by caesarean section and 35.9 percent by vaginal delivery. While 4.8% subjects had total bilirubin more than 15mg/dL, 68.3 percent had total bilirubin 10-15 mg/dL, and 26.9 percent had total bilirubin less than 10mg/dL. The cesarean section group showed a significant increase in total bilirubin.The group who had a caesarean section had a higher mean value (11.509) than the group that had a vaginal delivery (9.846). The two groups' mean differences are statistically significant (p is 0.000). Caesarean section coreelated with an elevated risk of infant jaundice, potentially generated by maternal anesthetic, particularly bupivacaine.